Аналітичне обґрунтування та моделювання технологій сушеної харчової продукції з органічної овочевої та плодово-ягідної сировини - Бідюк, Дмитро Олегович; Пономарьова, Людмила Миколаївна; Перцевой, Федір Всеволодович; Маренкова, Тетяна Іванівна (НТУ "ХПІ", 2017)
В статті розглянуто стан та перспективи розвитку світового та вітчизняного органічного виробництва, у тому числі овочевої та плодово-ягідної сировини. Проведено аналіз досліджень щодо виробництва сушеної харчової продукції з овочевої та плодово-ягідної сировини, у тому числі органічної. Досліджено асортимент вітчизняної органічної овочевої та плодово-ягідної сировини. Розроблено моделі інноваційної стратегії та технологічної системи отримання сушеної харчової продукції з органічної овочевої та плодово-ягідної сировини.

The article considers the state and trends in the modern world and Ukrainian markets of the cultivation, production, and processing of vegetable and fruit-berry raw materials of organic origin. Established base indices in the organic agriculture in the world and specified the geography of organic farms in Ukraine. The range of primary vegetable and fruit-berry raw materials of organic origin, which are zoned on the territory of Ukraine, is viewed. Relevance of vegetable and fruit and berry raw materials in dried form in the form of semi-finished products is justified. The analysis of recent researches of foreign and local scientists concerning the production of dried food products from vegetable and fruit and berry raw materials, including organic, is given. On the basis of theoretical preconditions, an analytical substantiation of the developed technologies is carried out. Parametric model "Black box" was developed. Given the systematic approach proposed of the model innovation strategies and technological system to obtain the dried food from organic vegetable and fruit-berry raw materials. Determined that the next step should be experimental studies both within each of the subsystems and the system as a whole.
Analytical substantiation and modeling of technologies for dried food products from organic vegetable and fruit-berry raw materials
Keywords: органічне виробництво; модель інноваційної стратегії; здорове харчування; аграрний сектор; ринок; organic production; technology modeling; innovation strategy